Positive electrode, preparation method thereof, and rechargeable lithium batteries
Patent Information
- Application Number
- KR1020250048278
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-14
- Publication Date
- 2026-10-21
Smart Images

Figure PAT00001_ABST
Abstract
Description
Technology Field
[0001] This invention relates to a positive electrode, a method for manufacturing a positive electrode, and a lithium secondary battery. Background Technology
[0002] Lithium-ion batteries, which offer high energy density and portability, are primarily used as the power source for mobile information terminals such as mobile phones, laptops, and smartphones. Recently, active research is being conducted to utilize high-energy-density lithium-ion batteries as power sources for driving or energy storage in hybrid and electric vehicles.
[0003] Various cathode active materials are being considered to realize lithium secondary batteries suitable for these applications. Among them, lithium nickel-based oxides, lithium nickel manganese cobalt composite oxides, lithium nickel cobalt aluminum composite oxides, and lithium cobalt oxides are primarily used as cathode active materials. With the recent surge in demand for large-capacity or high-energy-density lithium secondary batteries, there is a need to develop cathode active materials that simultaneously improve stability and performance, as well as cathodes containing such materials. The problem to be solved
[0004] We provide a cathode active material capable of realizing high density, high capacity, long lifespan characteristics, and high energy density, as well as a cathode and a lithium secondary battery applying the same. means of solving the problem
[0005] In one embodiment, the anode comprises a current collector; and an anode active material layer positioned on the current collector; wherein the anode active material layer comprises an anode active material, and the anode active material comprises a first anode active material containing a first lithium cobalt-based composite oxide having an aluminum content of 0.4 wt% or more relative to 100 wt% of the total metal excluding lithium; and a second anode active material containing a second lithium cobalt-based composite oxide having an aluminum content of 0.5 wt% or more relative to 100 wt% of the total metal excluding lithium; and the average particle size (D) of the first anode active material 50 ) is the average particle size (D) of the second positive active material above. 50 A positive electrode is provided that is greater than ) and, with respect to the total sum of the first positive electrode active material and the second positive electrode active material of 100 weight%, contains 70 weight% to 90 weight% of the first positive electrode active material and 10 weight% to 30 weight% of the second positive electrode active material, and has a ratio of the peak intensity of the (006) plane to the peak intensity of the (101) plane when measuring the X-ray diffraction pattern of the positive electrode of 4.0 or more.
[0006] In another embodiment, (i) a step of preparing a first positive electrode active material containing a first lithium cobalt-based oxide having an aluminum content of 0.4 mol% or more relative to 100 mol% of the total metal excluding lithium; (ii) containing a second lithium cobalt-based oxide having an aluminum content of 0.5 mol% or more relative to 100 mol% of the total metal excluding lithium, and the average particle size (D) of the first positive electrode active material 50 Average particle size (D) compared to ) 50(iii) a step of preparing a second positive active material; (iii) a step of preparing a positive composition by mixing 70% to 90% by weight of the first positive active material, 10% to 30% by weight of the second positive active material, and Al(OH)3 with respect to 100% by weight of the total of the first positive active material and the second positive active material; (iv) a step of manufacturing a positive by coating and drying the positive composition on a current collector; and (v) a step of first rolling the positive.
[0007] In another embodiment, a lithium secondary battery comprising the anode; cathode; and electrolyte is provided. Effects of the invention
[0008] The cathode according to one embodiment maximizes capacity, ensuring long lifespan characteristics and improving high voltage performance and high-temperature storage characteristics. A lithium secondary battery applying the cathode can exhibit high initial charge / discharge capacity and efficiency, achieve high energy density, and achieve long lifespan characteristics. Brief explanation of the drawing
[0009] FIGS. 1 to 4 are schematic drawings illustrating a lithium secondary battery according to one embodiment. Specific details for implementing the invention
[0010] Specific embodiments are described below in detail so that those skilled in the art can easily implement them. However, the present invention may be implemented in various different forms and is not limited to the embodiments described herein.
[0011] The terms used herein are for describing exemplary embodiments only and are not intended to limit the invention. Singular expressions include plural expressions unless the context clearly indicates otherwise.
[0012] Here, "combinations of these" refers to mixtures of components, laminates, composites, copolymers, alloys, blends, reaction products, etc.
[0013] The terms "include," "equip," or "have" used herein are intended to specify the existence of the implemented features, numbers, steps, components, or combinations thereof, and should be understood as not excluding in advance the existence or addition of one or more other features, numbers, steps, components, or combinations thereof.
[0014] In the drawings, thicknesses have been enlarged to clearly represent various layers and regions, and the same reference numerals have been used for similar parts throughout the specification. When a part such as a layer, film, region, or plate is described as being "on" or "on" another part, this includes not only cases where it is "immediately on" another part, but also cases where there is another part in between. Conversely, when a part is described as being "immediately on" another part, it means that there is no other part in between.
[0015] In addition, the term “layer” here includes not only the shape formed on the entire surface when viewed in a plan view, but also the shape formed on some surfaces.
[0016] The average particle size can be measured by methods widely known to those skilled in the art, for example, by measuring with a particle size analyzer, or by using transmission electron microscope or scanning electron microscope images. Alternatively, the average particle size value can be obtained by measuring using dynamic light scattering, performing data analysis to count the number of particles for each particle size range, and then calculating from this. Unless otherwise defined, the average particle size is the diameter (D) of the particle at which the cumulative volume in the particle size distribution is 50 volume%. 50It may mean ). In addition, unless otherwise defined, the average particle size is obtained by measuring the size (diameter or length of the major axis) of approximately 20 randomly selected particles from scanning electron microscope images to obtain a particle size distribution, and the diameter (D) of the particle with a cumulative volume of 50% in the said particle size distribution. 50 It may be that ) was taken as the average particle size.
[0017] Here, “or” is not interpreted in an exclusive sense; for example, “A or B” is interpreted to include A, B, A+B, etc.
[0018] The term “metal” is interpreted as a concept that includes common metals, transition metals, and metalloids (semimetals).
[0019] anode
[0020] In one embodiment, the anode comprises a current collector; and an anode active material layer located on the current collector; wherein the anode active material layer comprises an anode active material, and the anode active material comprises a first anode active material containing a first lithium cobalt-based composite oxide having an aluminum content of 0.4 wt% or more relative to 100 wt% of the total metal excluding lithium; and a second anode active material containing a second lithium cobalt-based composite oxide having an aluminum content of 0.5 wt% or more relative to 100 wt% of the total metal excluding lithium; and the average particle size (D) of the first anode active material 50 ) is the average particle size (D) of the second positive active material above. 50 A positive electrode is provided that is greater than ) and, with respect to the total sum of the first positive electrode active material and the second positive electrode active material of 100 weight%, contains 70 weight% to 90 weight% of the first positive electrode active material and 10 weight% to 30 weight% of the second positive electrode active material, and has a ratio of the peak intensity of the (006) plane to the peak intensity of the (101) plane when measuring the X-ray diffraction pattern of the positive electrode of 4.0 or more.
[0021] In one embodiment, a positive electrode active material containing a lithium cobalt-based composite oxide is used, and the average particle size (D 50 The present invention provides a positive electrode active material and a positive electrode containing the same, which successfully improves capacity and lifespan characteristics by using a positive electrode active material containing a different lithium cobalt-based composite oxide, finely controlling the content of each and the content of doping elements to ensure structural stability, and simultaneously manufacturing a high-density positive electrode through multi-stage rolling.
[0022] positive electrode active material
[0023] We are manufacturing cathode active materials with excellent stability at high voltages by doping with heterogeneous elements to prevent shrinkage and expansion caused by charging and discharging within the cathode active material and to stabilize the structure that could collapse due to the rearrangement of the layered structure. In particular, to enhance the structural stability of lithium cobalt-based oxides used as cathode active materials, Al 3+ and / or Mg 2+ Doping can be used. Al 3+ is Co 3+ Ion size similar to (Al 3+ : 0.535 Å, Co 3+ It has an oxidation state of 0.545 Å and is easy to use as a doping material because it has the same oxidation state. In addition, it possesses an Al-O bond energy (511±3 kJ / mol) that is stronger than the Co-O bond energy (384.5±13.4 kJ / mol). Aluminum has the advantage of being usable as a doping material because, even without participating in electrochemical reactions, it can maintain the structure of the cathode active material during contraction and expansion caused by charging and discharging, thereby suppressing structural changes in the cathode active material due to the movement of lithium ions. Furthermore, Mg 2+ It is substituted at lithium sites when doped and can prevent the rearrangement of the oxygen layer during charging and discharging in the lithium layer, thereby having the advantage of increasing structural stability.
[0024] In one embodiment, the average particle size (D 50 The present invention provides a cathode active material that succeeds in securing structural stability at high voltage and simultaneously improving capacity at high voltage, charge / discharge efficiency, and high-temperature life characteristics by mixing two different types of lithium cobalt-based cathode active materials, finely controlling the content of aluminum doped into each of the large and small particles, improving dispersibility during dry mixing of the cathode active material, and controlling rolling conditions during cathode manufacturing.
[0025] First positive active material
[0026] The first positive electrode active material contains a first lithium cobalt-based composite oxide, and may contain, for example, a first lithium cobalt-based oxide doped with aluminum and optionally magnesium, and the first lithium cobalt-based oxide can be represented by the following chemical formula 1.
[0027] [Chemical Formula 1]
[0028] Li a1 Co x1 Mg y1 Al z1 M 1 w1 O 2-b1 X b1
[0029] In Chemical Formula 1, 0.8≤a1≤1.5, 0.9≤x1≤0.99, 0≤y1≤0.05, 0.01≤z1≤0.04, 0≤w1≤0.01, 0.9≤x1+y1+z1+w1≤1.1, and 0≤b1≤0.1, and M 1 is one or more of the elements B, Ba, Ca, Ce, Cr, Cu, Fe, Mn, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, Zn and Zr, and X is one or more of the elements F, P and S.
[0030] In Chemical Formula 1, for example, 0.92≤x1≤0.98, 0.01≤y1≤0.04, 0.01≤z1≤0.03 and 0≤w1≤0.01, or 0.94≤x1≤0.98, 0.01≤y1≤0.03, 0.01≤z1≤0.02 and 0≤w1≤0.01. Also, 0.8≤a1≤1.2, 0.9≤a1≤1.2, or 0.98≤a1≤1.1.
[0031] The first positive active material containing the first lithium cobalt-based oxide can be expressed as an opposite or an allotrope. The average particle size (D) of the first positive active material 50 ) may be 9 μm to 30 μm, for example, 9 μm to 25 μm, 10 μm to 25 μm, or 12 μm to 20 μm. Here, the average particle size (D) of the first positive electrode active material is 50 ) is the average particle size (D) of the second positive active material to be described later. 50 It is larger than ). The positive active material according to one embodiment is in the form of a mixture of a first positive active material which is an opposite and a second positive active material which is a subatomic particle described later, and accordingly, the density of the positive active material layer (composite density) can be improved, and high capacity and high energy density can be realized. The average particle size (D) of the first positive active material 50 ) and the average particle size (D) of the second positive electrode active material 50 ) may be obtained by measuring the particle sizes (diameter or the length of the longest axis) of approximately 20 random particles in a scanning electron microscope image to obtain a particle size distribution, and taking the diameter of the particle with a cumulative volume of 50% of the particle size distribution as the average particle size.
[0032] In the first lithium cobalt-based composite oxide, the aluminum content (i.e., doping amount) relative to 100 wt% of the total metal excluding lithium is 0.4 wt% or more (4000 ppm or more), and may be, for example, 0.45 wt% or more, 0.5 wt% or more, 0.55 wt% or more, 0.6 wt% or more, or 0.65 wt% or more, and may be 2.0 wt% or less, 1.8 wt% or less, 1.6 wt% or less, 1.4 wt% or less, 1.2 wt% or less, 1.0 wt% or less, 0.8 wt% or less, or 0.75 wt% or less. When the aluminum doping amount in the first lithium cobalt-based oxide satisfies the above range, the cathode active material containing it is structurally stable at high voltage, and the capacity, resistance, and high-temperature life characteristics can all be improved.
[0033] For example, the first lithium cobalt-based oxide may further contain magnesium. The magnesium content relative to 100 wt% of the total metal excluding lithium in the first lithium cobalt-based composite oxide may be 2.0 wt% or less, for example, 1.0 wt% or less, 0.5 wt% or less, 0.15 wt% or less, 0.14 wt% or less, or 0.13 wt% or less, and may be 0.01 wt% or more, for example, 0.02 wt% or more, 0.03 wt% or more, 0.04 wt% or more, or 0.05 wt% or more. When the doping amount of magnesium in the first lithium cobalt-based oxide satisfies the above range, the cathode active material containing it may be structurally stable at high voltage, and the capacity, resistance, and lifespan characteristics may all be improved.
[0034] In one embodiment, the first positive active material may be included in an amount of 70% to 90% by weight, for example, 75% to 85% by weight, relative to 100% by weight of the total amount of the first positive active material and the second positive active material. When the content of the first positive active material is as described above, the positive active material containing it can achieve a high capacity, improve composite density, and exhibit a high energy density.
[0035] In one embodiment, the first positive active material may include a coating layer located on the surface of a particle containing aluminum, titanium, or a combination thereof, and the coating layer located on the surface of the first positive active material particle may be in the form of a shell that continuously surrounds the surface of the first positive active material particle, for example, in the form of a shell that surrounds the entire surface of the first positive active material particle. According to one embodiment, the coating layer may be formed in a form that continuously surrounds the surface of the first positive active material particle while being formed with a very thin and uniform thickness, and accordingly, the resistance of the positive active material does not increase or the capacity does not decrease, structural stability is improved, side reactions with the electrolyte can be effectively suppressed, the amount of gas generated under high voltage and high temperature conditions is reduced, and long life characteristics can be realized.
[0036] In one embodiment, the thickness of the coating layer located on the surface of the first positive active material particle may be 5 nm to 200 nm, for example, 5 nm to 150 nm, 5 nm to 100 nm, 5 nm to 80 nm, 5 nm to 50 nm, or 10 nm to 50 nm. When the coating layer satisfies the above thickness range, the structural stability of the positive active material can be improved and side reactions with the electrolyte can be effectively suppressed without increasing resistance or decreasing capacity due to the coating. The thickness of the coating layer can be measured, for example, through SEM, TEM, TOF-SIMS, XPS, or EDS analysis, and for example, through EDS line profile analysis of the cross-section of the positive active material.
[0037] In one embodiment, the coating layer is characterized by being thin with a thickness of tens to hundreds of nanometers and having a uniform thickness. For example, the variation in coating layer thickness within a single positive active material particle may be 20% or less, 18% or less, or 15% or less. Here, the variation in coating layer thickness refers to the thickness of the coating layer within a single positive active material particle. The variation in coating layer thickness may mean, for example, measuring the thickness at about 10 points in an electron microscope image of a cross-section of a single positive active material particle, calculating the arithmetic mean, dividing the absolute value of the difference between one data point and the arithmetic mean value by the arithmetic mean value, and multiplying by 100. When the variation or standard deviation of the coating layer thickness satisfies the above range, it means that a coating layer of uniform thickness is formed in a good form on the surface of the positive active material particle. Accordingly, the structural stability of the positive active material is improved, side reactions with the electrolyte are effectively suppressed, and the increase in resistance or decrease in capacity caused by the coating can be minimized.
[0038] Second positive active material
[0039] The second positive electrode active material contains a second lithium cobalt-based composite oxide, and may contain, for example, a second lithium cobalt-based oxide doped with aluminum and optionally magnesium, and the second lithium cobalt-based oxide can be represented by the following chemical formula 2.
[0040] [Chemical Formula 2]
[0041] Li a2 Co x2 Mg y2 Al z2 M 2 w2 O 2-b2 X b2
[0042] In Chemical Formula 2, 0.8≤a2≤1.5, 0.9≤x2≤0.99, 0≤y2≤0.05, 0.01≤z2≤0.04, 0≤w2≤0.01, 0.9≤x2+y2+z2+w2≤1.1, and 0≤b2≤0.1, and M 2 is one or more of the elements B, Ba, Ca, Ce, Cr, Cu, Fe, Mn, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, Zn and Zr, and X is one or more of the elements F, P and S.
[0043] In Chemical Formula 2, for example, 0.92≤x2≤0.98, 0.01≤y2≤0.04, 0.01≤z2≤0.03 and 0≤w2≤0.01, or 0.94≤x2≤0.98, 0.01≤y2≤0.03, 0.01≤z2≤0.02 and 0≤w2≤0.01. Also, 0.8≤a2≤1.2, 0.9≤a2≤1.2, or 0.98≤a2≤1.1.
[0044] The second positive active material containing the second lithium cobalt-based oxide can be expressed as fine particles or small particles. The average particle size (D) of the second positive active material. 50 ) can be 1 μm to 9 μm, for example, 1 μm to 8 μm, or 2 μm to 6 μm. Here, the average particle size (D) of the second positive active material is 50 ) is the average particle size (D) of the aforementioned first positive active material.50 It is smaller than ). The positive active material according to one embodiment is in the form of a mixture of a first positive active material that is an opposite and a second positive active material that is a subatomic particle, and accordingly, the density of the positive active material layer can be improved, and high capacity and high energy density can be realized. The average particle size (D) of the second positive active material. 50 ) and the average particle size (D) of the second positive electrode active material 50 ) may be obtained by measuring the particle sizes (diameter or the length of the longest axis) of approximately 20 random particles in a scanning electron microscope image to obtain a particle size distribution, and taking the diameter of the particle with a cumulative volume of 50% of the particle size distribution as the average particle size.
[0045] The content of aluminum (i.e., doping amount) relative to 100 wt% of the total metal excluding lithium in the second lithium cobalt-based composite oxide is 0.5 wt% or more (5000 ppm or more), and may be, for example, 0.55 wt% or more, 0.6 wt% or more, 0.65 wt% or more, 0.7 wt% or more, or 0.75 wt% or more, and may be 2.0 wt% or less, 1.8 wt% or less, 1.6 wt% or less, 1.4 wt% or less, 1.2 wt% or less, 1.0 wt% or less, 0.8 wt% or less, or 0.75 wt% or less. When the doping amount of aluminum in the second lithium cobalt-based oxide satisfies the above range, the cathode active material containing it is structurally stable at high voltage, and the capacity, resistance, and high-temperature life characteristics can all be improved.
[0046] For example, the second lithium cobalt-based oxide may further contain magnesium. The magnesium content relative to 100 wt% of the total metal excluding lithium in the second lithium cobalt-based composite oxide may be 2.0 wt% or less, for example, 1.0 wt% or less, 0.5 wt% or less, 0.15 wt% or less, 0.14 wt% or less, or 0.13 wt% or less, and may be 0.01 wt% or more, for example, 0.02 wt% or more, 0.03 wt% or more, 0.04 wt% or more, or 0.05 wt% or more. When the doping amount of magnesium in the second lithium cobalt-based oxide satisfies the above range, the cathode active material containing it may be structurally stable at high voltage, and the capacity, resistance, and lifespan characteristics may all be improved.
[0047] In one embodiment, the amount of aluminum doped in the second lithium cobalt-based oxide may be greater than the amount of aluminum doped in the first lithium cobalt-based oxide, and the amount of aluminum doped in the second lithium cobalt-based oxide may be 0.05 wt% or more, for example, 0.05 wt% to 0.50 wt%, 0.05 wt% to 0.45 wt%, 0.05 wt% to 0.40 wt%, 0.05 wt% to 0.35 wt%, or 0.05 wt% to 0.30 wt% more than the amount of aluminum doped in the first lithium cobalt-based oxide. In this case, the cathode active material containing these materials can maintain a very stable structure even when charging and discharging are repeated at high voltage, and the capacity, resistance, and room temperature / high temperature life characteristics can all be improved.
[0048] In one embodiment, the second positive active material may be included in an amount of 10% to 30% by weight, for example, 15% to 25% by weight, relative to 100% by weight of the total first positive active material and second positive active material. When the content of the second positive active material is as described above, the positive active material containing it can achieve a high capacity, improve composite density, and exhibit a high energy density.
[0049] In one embodiment, the second positive active material may include a coating layer located on the surface of a particle containing aluminum, titanium, or a combination thereof, and the coating layer located on the surface of the second positive active material particle may be in the form of a shell that continuously surrounds the surface of the second positive active material particle, for example, in the form of a shell that surrounds the entire surface of the second positive active material particle. According to one embodiment, the coating layer may be formed in a form that continuously surrounds the surface of the second positive active material particle while being formed with a very thin and uniform thickness, and accordingly, the resistance of the positive active material does not increase or the capacity does not decrease, structural stability is improved, side reactions with the electrolyte can be effectively suppressed, the amount of gas generated under high voltage and high temperature conditions is reduced, and long life characteristics can be realized.
[0050] In one embodiment, the thickness of the coating layer located on the surface of the second positive active material particle may be 5 nm to 200 nm, for example, 5 nm to 150 nm, 5 nm to 100 nm, 5 nm to 80 nm, 5 nm to 50 nm, or 10 nm to 50 nm. When the coating layer satisfies the above thickness range, the structural stability of the positive active material can be improved and side reactions with the electrolyte can be effectively suppressed without increasing resistance or decreasing capacity due to the coating. The thickness of the coating layer can be measured, for example, through SEM, TEM, TOF-SIMS, XPS, or EDS analysis, and for example, through EDS line profile analysis of the cross-section of the positive active material.
[0051] In one embodiment, the coating layer is characterized by being thin with a thickness of tens to hundreds of nanometers and having a uniform thickness. For example, the variation in coating layer thickness within a single positive active material particle may be 20% or less, 18% or less, or 15% or less. Here, the variation in coating layer thickness refers to the thickness of the coating layer within a single positive active material particle. The variation in coating layer thickness may mean, for example, measuring the thickness at about 10 points in an electron microscope image of a cross-section of a single positive active material particle, calculating the arithmetic mean, dividing the absolute value of the difference between one data point and the arithmetic mean value by the arithmetic mean value, and multiplying by 100. When the variation or standard deviation of the coating layer thickness satisfies the above range, it means that a coating layer of uniform thickness is formed in a good form on the surface of the positive active material particle. Accordingly, the structural stability of the positive active material is improved, side reactions with the electrolyte are effectively suppressed, and the increase in resistance or decrease in capacity caused by the coating can be minimized.
[0052] In one embodiment, the apparatus comprises a current collector; and a positive active material layer located on the current collector; wherein the positive active material layer comprises the aforementioned positive active material, and the positive active material layer may further comprise other types of positive active materials in addition to the aforementioned positive active material. Additionally, the positive active material layer may optionally further comprise a binder, a conductive material, or a combination thereof.
[0053] In one embodiment, when measuring the X-ray diffraction (XRD) pattern of the anode, the ratio of the peak intensity of the (006) plane to the peak intensity of the (101) plane is 4.0 or higher. At this time, when measuring the X-ray diffraction (XRD) pattern of the anode, the peak of the (101) plane refers to the peak at a diffraction angle 2θ = 37.5° ± 0.5° in the XRD spectrum, and the peak intensity refers to the value on the vertical axis of the peak.
[0054] The above peak intensity ratio may be a value obtained after coating and drying an anode composition comprising a first anode active material and a second anode active material on the current collector, and performing a first rolling process to form an anode active material layer, or a value obtained after additionally performing a second rolling process, etc., after the first rolling process to form an anode active material layer. The peak intensity ratio (I) obtained at this time (006) / I (110) ) is 4.0 or greater, and may be, for example, 4.0 to 6.0, or 4.1 to 5.4. Peak intensity ratio (I (006) / I (110) When ) is included in the above range, the shortened lithium ion migration distance and ion resistance are reduced, and the orientation of the cathode active material particles within the cathode changes, thereby changing the crystallinity and optimizing the density of the cathode to achieve high capacity, long lifespan characteristics, and high energy density.
[0055] In addition, the peak intensity ratio (I) of the coating layer coated and dried with the anode composition before the first rolling process. (006) / I (110)) may be less than 4.0, for example, between 0.1 and 4.0. In this way, when the peak intensity ratio (I(006) / I(110)) before and after the rolling process is each included in the above range, the shortened lithium ion migration distance and ion resistance are reduced, and the crystallinity changes as the orientation of the positive active material particles in the positive electrode changes, thereby optimizing the density of the positive electrode to achieve high capacity, long lifespan characteristics, and high energy density.
[0056] In one embodiment, XRD measurement can be performed using a New Bruker D8 XRD instrument with CuKα as the target line and using an area method utilizing Fullprof. At this time, the measurement conditions can be 2θ = 10° to 80°, 0.02 sec / step to 0.08 sec / step, and the step size can be 0.01° / step to 0.03° / step.
[0057] I for the anode according to one embodiment (006) / I (110) The peak intensity ratio can be designed to be in the range of 4.0 or higher by adjusting the composition of the first and second positive active materials, for example, the aluminum doping content, adjusting the mixing ratio of the first and second positive active materials, adjusting the dispersibility when dry mixing the first and second positive active materials, and / or adjusting the pressurization conditions, pressurization method, number of pressurizations, etc., during positive manufacturing.
[0058] According to one embodiment, the loading level of the positive active material layer is 10 mg / cm² 2 to 40 mg / cm² 2 It could be, for example, 10 mg / cm² 2 to 30 mg / cm² 2 or 10 mg / cm² 2 to 20 mg / cm² 2In addition, the density of the positive active material layer in the rolled final positive electrode may be 4.2 g / cc to 4.5 g / cc, for example, 4.2 g / cc to 4.4 g / cc, 4.2 g / cc to 4.3 g / cc, or 4.23 g / cc to 4.27 g / cc. When applying the positive active material according to one embodiment, it is advantageous to achieve such loading levels and the density of the positive active material layer, and a positive electrode satisfying the loading levels and positive electrode densities within the above range is suitable for realizing a high-capacity, high-energy-density lithium secondary battery. The density of the positive active material layer refers to the ratio of weight to volume of the positive active material layer in the rolled positive electrode. The density of the positive active material layer can be measured by measuring the cross-sectional area, thickness, and weight of the positive active material layer excluding the current collector, calculating the volume by multiplying the cross-sectional area and thickness, and dividing the weight by the volume.
[0059] According to one embodiment, the positive active material layer may further include aluminum hydroxide, aluminum oxide, or a combination thereof in addition to the first positive active material and the second positive active material, and may further include Al(OH)3 as an example. According to the method for manufacturing a positive electrode according to one embodiment, dispersibility can be improved and high-temperature characteristics of the battery can be enhanced by adding and mixing Al(OH)3 when dry mixing the first positive active material and the second positive active material. That is, by further including aluminum hydroxide, aluminum oxide, or a combination thereof, the processability of the positive active material layer can be improved and high-temperature characteristics of the battery, such as high-temperature life characteristics, can be enhanced.
[0060] bookbinder
[0061] The binder serves to adhere the positive active material particles well to each other and also to adhere the positive active material well to the current collector. Representative examples of binders include, but are not limited to, polyvinyl alcohol, carboxymethylcellulose, hydroxypropylcellulose, diacetylcellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylic resin, polyester resin, nylon, etc.
[0062] Challenge
[0063] A conductive material is used to impart conductivity to an electrode, and any electronically conductive material that does not cause chemical changes can be used in the battery being constructed. Examples of conductive materials include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, and carbon nanotube; metal-based materials containing copper, nickel, aluminum, silver, etc., in the form of metal powder or metal fibers; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0064] The content of the binder and the conductive material may be 0.5% to 5% by weight each with respect to 100% by weight of the positive active material layer.
[0065] Al thin films can be used as the current collector, but are not limited to this.
[0066] Method for manufacturing an anode
[0067] In one embodiment, (i) a step of preparing a first positive electrode active material containing a first lithium cobalt-based oxide having an aluminum content of 0.4 wt% or more relative to 100 wt% of the total metal excluding lithium; (ii) containing a second lithium cobalt-based oxide having an aluminum content of 0.5 wt% or more relative to 100 wt% of the total metal excluding lithium, and the average particle size (D) of the first positive electrode active material 50 Average particle size (D) compared to ) 50 (iii) a step of preparing a second positive active material; (iii) a step of preparing a positive composition by mixing 70% to 90% by weight of the first positive active material, 10% to 30% by weight of the second positive active material, and Al(OH)3 with respect to 100% by weight of the total of the first positive active material and the second positive active material; (iv) a step of manufacturing a positive by coating and drying the positive composition on a current collector; and (v) a step of first rolling the positive.
[0068] In one embodiment, a positive electrode active material containing a lithium cobalt-based composite oxide is used, and the average particle size (D 50 The present invention provides a method for manufacturing a cathode that successfully improves capacity, lifespan characteristics, etc., by using a cathode active material containing a different lithium cobalt-based composite oxide, simultaneously improving dispersibility when dry mixing heterogeneous cathode active materials, and manufacturing a high-density cathode through a rolling method.
[0069] The first positive electrode active material and the second positive electrode active material can each be manufactured by a method of mixing a lithium raw material with a precursor which is a cobalt complex hydroxide and / or a cobalt-based complex oxide and heat treating it. The heat treatment can be performed at a temperature of, for example, 800°C to 1100°C, 850°C to 1080°C, or 890°C to 1060°C, and can be carried out for 5 to 25 hours, for example, 8 to 15 hours.
[0070] The first lithium cobalt-based composite oxide can be prepared using the first cobalt-based composite oxide, and the first cobalt-based composite oxide can be represented by the following chemical formula 11; the second lithium cobalt-based composite oxide can be prepared using the second cobalt-based composite oxide, and the second cobalt-based composite oxide can be represented by the following chemical formula 12.
[0071] [Chemical Formula 11]
[0072] Co (3-y11-z11-w11) Mg y11 Al z11 M 11 w11 O 4-a
[0073] In Chemical Formula 11, 0≤y11≤0.05, 0.03≤z11≤0.12, 0≤w11≤0.01 and 0≤a≤0.5, and M 11 It is one or more of the elements B, Ba, Ca, Ce, Cr, Cu, Fe, Mn, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, Zn and Zr.
[0074] In Chemical Formula 11, for example, 0≤y11≤0.04, 0.036≤z11≤0.1 and 0≤w11≤0.01, or 0.01≤y11≤0.03, 0.036≤z11≤0.08 and 0≤w11≤0.01.
[0075] [Chemical Formula 12]
[0076] Co (3-y12-z12-w12) Mg y12 Al z12 M 12 w12 O 4-a
[0077] In Chemical Formula 12, 0≤y12≤0.05, 0.03≤z12≤0.12, 0≤w12≤0.01 and 0≤a≤0.5, and M 12 It is one or more of the elements B, Ba, Ca, Ce, Cr, Cu, Fe, Mn, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, Zn and Zr.
[0078] In Chemical Formula 12, for example, 0≤y12≤0.04, 0.051≤z12≤0.1 and 0≤w12≤0.01, or 0.01≤y12≤0.03, 0.051≤z12≤0.08 and 0≤w12≤0.01.
[0079] The first cobalt-based metal composite oxide may be in the form of particles and have an average particle size of 9 μm to 30 μm. The second cobalt-based metal composite oxide may be in the form of particles and have an average particle size of 1 μm to 9 μm.
[0080] The above lithium raw material may include lithium carbonate, lithium sulfate, lithium hydroxide, or anhydrous forms thereof.
[0081] The molar ratio of lithium in the lithium raw material to 1 mole of the total metal excluding lithium in the first and second positive active materials may be 0.8 to 1.5, 0.8 to 1.2, 0.9 to 1.2, or 0.98 to 1.1.
[0082] In one embodiment, a positive electrode composition is prepared by mixing 70% to 90% by weight of the first positive electrode active material, 10% to 30% by weight of the second positive electrode active material, and Al(OH)3 with respect to a total of 100% by weight of the first positive electrode active material and the second positive electrode active material. By adding Al(OH)3 when mixing the first positive electrode active material and the second positive electrode active material, the dispersibility can be improved, and through this, the density of the positive electrode active material layer can be increased, thereby increasing the ratio of the peak intensity of the (006) plane to the peak intensity of the (101) plane when measuring the X-ray diffraction (XRD) pattern of the positive electrode, and the high-temperature characteristics of the battery can be improved.
[0083] In step (iii) above, Al(OH)3 may be mixed in an amount of 0.01% to 0.1% by weight relative to 100% by weight of the total of the first and second positive active materials. When Al(OH)3 is added within the above content range, the dispersibility of the positive active materials can be improved without reducing the capacity of the battery, thereby increasing the positive density and improving processability, and the high-temperature characteristics of the battery can be improved.
[0084] In one embodiment, when measuring the X-ray diffraction (XRD) pattern of the anode, the ratio of the peak intensity of the (006) plane to the peak intensity of the (101) plane is 4.0 or higher. At this time, when measuring the X-ray diffraction (XRD) pattern of the anode, the peak of the (101) plane refers to the peak at a diffraction angle 2θ = 37.5° ± 0.5° in the XRD spectrum, and the peak intensity refers to the value on the vertical axis of the peak.
[0085] The above peak intensity ratio may be a value obtained after coating and drying an anode composition comprising a first anode active material and a second anode active material on the current collector, and performing a first rolling process to form an anode active material layer, or a value obtained after additionally performing a second rolling process, etc., after the first rolling process to form an anode active material layer. The peak intensity ratio (I) obtained at this time (006) / I (110) ) is 4.0 or greater, and may be, for example, 4.0 to 6.0, or 4.1 to 5.4. Peak intensity ratio (I (006) / I (110) When ) is included in the above range, the shortened lithium ion migration distance and ion resistance are reduced, and the orientation of the cathode active material particles within the cathode changes, thereby changing the crystallinity and optimizing the density of the cathode to achieve high capacity, long lifespan characteristics, and high energy density.
[0086] In addition, before the first rolling process, the peak intensity ratio (I(006) / I(110)) of the coating layer coated with the anode composition may be less than 4.0, for example, 0.1 to 4.0. Thus, when the peak intensity ratio (I(006) / I(110)) before and after the first rolling process falls within the above range, the shortened lithium ion migration distance and ion resistance are reduced, and the crystallinity changes as the orientation of the anode active material particles within the anode changes, thereby optimizing the density of the anode to achieve high capacity, long lifespan characteristics, and high energy density.
[0087] In one embodiment, XRD measurement was performed using CuKα as the target line, using a New Bruker D8 XRD instrument, and using an area method utilizing Fullprof. At this time, the measurement conditions can be 2θ = 10° to 80°, 0.02 sec / step to 0.08 sec / step, and the step size can be 0.01° / step to 0.03° / step.
[0088] In one embodiment, a second rolling process may be further performed after the first rolling, and additionally, a third rolling and a fourth rolling may be further performed. By applying rolling in multiple stages, it is possible to increase the density of the anode without causing degradation or cracking of the anode active material, and I according to one embodiment (006) / I (110) The peak intensity ratio can be increased.
[0089] For example, the first rolling may be applied so that the density of the positive active material layer satisfies a range of 4.0 g / cc to 4.2 g / cc, and the second rolling may be applied so that the density of the positive active material layer satisfies a range of 4.2 g / cc or more, for example, 4.25 g / cc to 4.5 g / cc.
[0090] In the final rolled anode, the density of the anode active material layer may be 4.2 g / cc to 4.5 g / cc, for example, 4.2 g / cc to 4.4 g / cc, 4.2 g / cc to 4.3 g / cc, or 4.23 g / cc to 4.27 g / cc.
[0091] lithium secondary battery
[0092] In one embodiment, a lithium secondary battery comprising the aforementioned positive electrode, negative electrode, and electrolyte is provided. As an example, the lithium secondary battery may include a positive electrode, a negative electrode, a separator located between the positive electrode and the negative electrode, and an electrolyte.
[0093] Lithium secondary batteries can be classified into cylindrical, prismatic, pouch, coin, etc., depending on their shape. FIGS. 1 to 4 are schematic diagrams illustrating a lithium secondary battery according to one embodiment, where FIG. 1 is a cylindrical battery, FIG. 2 is a prismatic battery, and FIGS. 3 and 4 are pouch-type batteries. Referring to FIGS. 1 to 4, the lithium secondary battery (100) may include an electrode assembly (40) having a separator (30) interposed between a positive electrode (10) and a negative electrode (20), and a case (50) in which the electrode assembly (40) is housed. The positive electrode (10), the negative electrode (20), and the separator (30) may be impregnated with an electrolyte (not shown). The lithium secondary battery (100) may include a sealing member (60) that seals the case (50) as in FIG. 1. In addition, in FIG. 2, the lithium secondary battery (100) may include a positive lead tab (11) and a positive terminal (12), a negative lead tab (21) and a negative terminal (22). As shown in FIG. 3 and FIG. 4, the lithium secondary battery (100) may include an electrode tab (70), namely a positive tab (71) and a negative tab (72), which serve as an electrical path to guide the current formed in the electrode assembly (40) to the outside.
[0094] cathode
[0095] The cathode may include a current collector; and a cathode active material layer located on the current collector; and the cathode active material layer may include a cathode active material and may further include a binder, a conductive material, or a combination thereof.
[0096] cathode active material
[0097] The negative electrode active material includes a material capable of reversibly intercalating / deintercalating lithium ions, lithium metal, an alloy of lithium metal, a material capable of doping and dedoping lithium, or a transition metal oxide.
[0098] A material capable of reversibly intercalating / deintercalating the above lithium ions may be a carbon-based negative electrode active material, such as crystalline carbon, amorphous carbon, or a combination thereof. Examples of the crystalline carbon include graphite such as amorphous, plate-like, flake-like, spherical, or fibrous natural graphite or artificial graphite, and examples of the amorphous carbon include soft carbon or hard carbon, mesophase pitch carbide, calcined coke, etc.
[0099] As the above lithium metal alloy, an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn may be used.
[0100] As a material capable of doping and undoping the above lithium, a Si-based negative electrode active material or a Sn-based negative electrode active material may be used. The above Si-based negative electrode active material may include silicon, silicon-carbon composites, and SiOx(0 <x≤2), Si-Q 합금(상기 Q는 알칼리 금속, 알칼리 토금속, 13족 원소, 14족 원소(Si를 제외함), 15족 원소, 16족 원소, 전이금속, 희토류 원소 및 이들의 조합에서 선택되는 원소이며, 예컨대 Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, 및 이들의 조합에서 선택됨), 또는 이들의 조합일 수 있다. 상기 Sn계 음극 활물질로는 Sn, SnO2, Sn 합금 또는 이들의 조합일 수 있다.
[0101] The above silicon-carbon composite may be a composite of silicon and amorphous carbon. The average particle size (D) of the silicon-carbon composite particles 50 ) can be, for example, 0.5 μm to 20 μm. According to one embodiment, the silicon-carbon composite may be in the form of silicon particles and amorphous carbon coated on the surface of the silicon particles. For example, it may include a secondary particle (core) assembled from silicon primary particles and an amorphous carbon coating layer (shell) located on the surface of the secondary particle. The amorphous carbon may also be located between the silicon primary particles, so that, for example, the silicon primary particles may be coated with amorphous carbon. The secondary particles may be dispersed in an amorphous carbon matrix.
[0102] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include a core comprising crystalline carbon and silicon particles and an amorphous carbon coating layer located on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. Examples of the amorphous carbon include soft carbon or hard carbon, mesophase pitch carbide, calcined coke, etc.
[0103] When the silicon-carbon composite comprises silicon and amorphous carbon, the silicon content may be 10% to 50% by weight with respect to 100% by weight of the silicon-carbon composite, and the amorphous carbon content may be 50% to 90% by weight. Additionally, when the composite comprises silicon, amorphous carbon, and crystalline carbon, the silicon content may be 10% to 50% by weight with respect to 100% by weight of the silicon-carbon composite, the crystalline carbon content may be 10% to 70% by weight, and the amorphous carbon content may be 20% to 40% by weight.
[0104] In addition, the thickness of the amorphous carbon coating layer may be 5 nm to 100 nm. The average particle size (D) of the silicon particles (primary particles) 50 ) can be 10 nm to 1 µm, or 10 nm to 200 nm. The silicon particles may exist as silicon alone, in the form of a silicon alloy, or in an oxidized form. The oxidized form of silicon is SiO x (0 <x≤2)로 표시될 수 있다. 이때, 산화 정도를 나타내는 Si:O의 원자 함량 비율은 99:1 내지 33:67일 수 있다. 본 명세서에서, 별도의 정의가 없는 한, 평균 입경(D 50 ) refers to the diameter of the particle with a cumulative volume of 50 volume% in the particle size distribution.
[0105] The above Si-based negative electrode active material or Sn-based negative electrode active material may be used in combination with a carbon-based negative electrode active material. When the Si-based negative electrode active material or Sn-based negative electrode active material and the carbon-based negative electrode active material are mixed and used, the mixing ratio may be 1:99 to 90:10 by weight.
[0106] bookbinder
[0107] The above binder serves to effectively bond the negative electrode active material particles to each other and also to effectively bond the negative electrode active material to the current collector. As the binder, a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof may be used.
[0108] Examples of non-aqueous binders include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide imide, polyimide, or combinations thereof.
[0109] The water-based binder may be selected from styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylenepropylenediene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.
[0110] When a water-based binder is used as the cathode binder, a cellulose-based compound capable of imparting viscosity may be further included. As this cellulose-based compound, one or more types such as carboxymethyl cellulose, hydroxypropylmethyl cellulose, methyl cellulose, or alkali metal salts thereof may be mixed and used. Na, K, or Li may be used as the alkali metal.
[0111] The dry binder is a polymer material capable of fiberization, and may be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or a combination thereof.
[0112] Challenge
[0113] A conductive material is used to impart conductivity to an electrode, and any electronically conductive material that does not cause chemical changes can be used in the battery being constructed. Specific examples include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjenblack, carbon fiber, carbon nanofiber, and carbon nanotube; metal-based materials in the form of metal powder or metal fibers including copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0114] The content of the negative electrode active material may be 95% to 99.5% by weight with respect to 100% by weight of the negative electrode active material layer, and the content of the binder may be 0.5% to 5% by weight with respect to 100% by weight of the negative electrode active material layer. For example, the negative electrode active material layer may contain 90% to 99% by weight of the negative electrode active material, 0.5% to 5% by weight of the binder, and 0.5% to 5% by weight of the conductive material.
[0115] The whole house
[0116] The negative current collector may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or alloys thereof, and may be in the form of a foil, sheet, or foam. The thickness of the negative current collector may be, for example, 1 μm to 20 μm, 5 μm to 15 μm, or 7 μm to 10 μm.
[0117] electrolytes
[0118] The electrolyte for a lithium secondary battery may be, for example, an electrolyte solution, which may include a non-aqueous organic solvent and a lithium salt.
[0119] Non-aqueous organic solvents serve as a medium through which ions involved in the electrochemical reaction of a cell can move. Non-aqueous organic solvents may be carbonate-based, ester-based, ether-based, ketone-based, or alcohol-based solvents, aprotic solvents, or a combination thereof.
[0120] Carbonate-based solvents that may be used include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Ester-based solvents that may be used include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methylpropionate, ethylpropionate, decanolide, mevalonolactone, valerolactone, caprolactone, etc. As ether-based solvents, dibutyl ether, tetraglame, diglame, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. may be used. Additionally, as ketone-based solvents, cyclohexanone, etc. may be used. As alcohol-based solvents, ethyl alcohol, isopropyl alcohol, etc. may be used, and as aprotic solvents, nitriles such as R-CN (where R is a straight-chain, branched, or cyclic hydrocarbon group having 2 to 20 carbon atoms and may include a double bond, an aromatic ring, or an ether group); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane, 1,4-dioxolane; sulfolanes, etc. may be used.
[0121] Non-aqueous organic solvents may be used alone or in a mixture of two or more types, and when two or more types are mixed, the mixing ratio can be appropriately adjusted according to the desired battery performance, which is widely understood by those working in the field.
[0122] When using a carbonate-based solvent, a mixture of cyclic carbonates and chain carbonates can be used, and the cyclic carbonates and chain carbonates can be mixed in a volume ratio of 1:1 to 1:9.
[0123] The non-aqueous organic solvent may further include an aromatic hydrocarbon-based organic solvent. For example, a carbonate-based solvent and an aromatic hydrocarbon-based organic solvent may be mixed and used in a volume ratio of 1:1 to 30:1.
[0124] The electrolyte may further include vinyl ethyl carbonate, vinylene carbonate, or ethylene carbonate-based compounds to improve battery life.
[0125] Representative examples of the above ethylene carbonate compounds include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.
[0126] Lithium salts are substances that dissolve in organic solvents and act as a source of lithium ions within the battery, enabling the basic operation of rechargeable lithium batteries and facilitating the movement of lithium ions between the anode and cathode. Representative examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, and LiN(C x F 2x+1 SO2)(C y F 2y+1 It may include one or more selected from SO2)(x and y are integers from 1 to 20), lithium trifluoromethane sulfonate, lithium tetrafluoroethane sulfonate, lithium difluorobis(oxalate)phosphate (LiDFBOP), and lithium bis(oxalate)borate (LiBOB).
[0127] It is preferable to use a lithium salt concentration within the range of 0.1M to 2.0M. When the lithium salt concentration falls within the above range, the electrolyte has appropriate ionic conductivity and viscosity, so it can exhibit excellent performance and lithium ions can move effectively.
[0128] separator
[0129] Depending on the type of lithium secondary battery, a separator may be present between the positive and negative electrodes. As such a separator, polyethylene, polypropylene, polyvinylidene fluoride, or multilayer films of two or more layers thereof may be used, and of course, mixed multilayer films such as polyethylene / polypropylene two-layer separators, polyethylene / polypropylene / polyethylene three-layer separators, and polypropylene / polyethylene / polypropylene three-layer separators may be used.
[0130] The above separator may include a porous substrate and a coating layer comprising an organic material, an inorganic material, or a combination thereof located on one or both sides of the porous substrate.
[0131] The porous substrate may be a polymer membrane formed from any one of the following: polyolefins such as polyethylene and polypropylene; polyesters such as polyethylene terephthalate and polybutylene terephthalate; polyacetal; polyamide; polyimide; polycarbonate; polyetherketone; polyaryletherketone; polyetherimide; polyamideimide; polybenzimidazole; polyethersulfone; polyphenylene oxide; cyclic olefin copolymer; polyphenylene sulfide; polyethylene naphthalate; glass fiber; Teflon; and polytetrafluoroethylene, or a copolymer or mixture of two or more of these.
[0132] The porous substrate may have a thickness of about 1 μm to 40 μm, and may have a thickness of, for example, 1 μm to 30 μm, 1 μm to 20 μm, 5 μm to 15 μm, or 10 μm to 15 μm.
[0133] The above organic material may include a (meth)acrylic copolymer comprising a first structural unit derived from (meth)acrylamide, and a second structural unit comprising at least one of a structural unit derived from (meth)acrylic acid or (meth)acrylate and a structural unit derived from (meth)acrylamideidosulfonic acid or its salt.
[0134] The above inorganic materials are Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, It may include inorganic particles selected from SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof, but is not limited thereto. The average particle size (D) of the inorganic particles. 50 ) can be 1 nm to 2000 nm, and, for example, 100 nm to 1000 nm, or 100 nm to 700 nm.
[0135] The above organic and inorganic materials may exist mixed in a single coating layer, or may exist in a stacked form with a coating layer containing organic materials and a coating layer containing inorganic materials.
[0136] The thickness of the coating layer may be 0.5 μm to 20 μm, for example, 1 μm to 10 μm, or 1 μm to 5 μm.
[0138] Examples and comparative examples of the present invention are described below. The following examples are merely illustrative of the present invention, and the present invention is not limited to the following examples.
[0139] Example 1
[0140] 1. Preparation of cathode active material
[0141] A first cobalt transition metal complex oxide (Co0.983 Al 0.017 By mixing O2) and Li2CO3 such that the molar ratio of the total metal of the first cobalt transition metal complex oxide to the lithium of Li2CO3 is 1:1.04, and heat-treating at approximately 1050°C for 10 hours in an air atmosphere, the average particle size (D 50 A first lithium cobalt-based oxide (Li) having a content of 18 μm. 1.04 Co 0.983 Al 0.017 A first positive active material containing O2 was prepared.
[0142] A second cobalt transition metal complex oxide (Co 0.979 Al 0.021 By mixing O2) and Li2CO3 such that the molar ratio of the total metal of the second cobalt transition metal complex oxide to the lithium of Li2CO3 is 1:1.02, and heat-treating at approximately 900°C for 10 hours in an air atmosphere, the average particle size (D 50 A second lithium cobalt-based oxide (Li) having a content of approximately 4 μm. 1.02 Co 0.979 Al 0.021 A second positive active material containing O2 was prepared.
[0143] A positive electrode active material was prepared by dry mixing 80 wt% of the first positive electrode active material, 20 wt% of the second positive electrode active material, and Al(OH)3. At this time, 0.01 wt% of Al(OH)3 was added to a total of 100 wt% of the first positive electrode active material and the second positive electrode active material.
[0144] 2. Manufacture of lithium secondary batteries
[0145] A cathode active material layer slurry was prepared by mixing 98.5 wt% of the manufactured cathode active material, 1.0 wt% of a polyvinylidene fluoride binder, and 0.5 wt% of a carbon nanotube conductive material, and the slurry was coated onto an aluminum foil current collector, dried, and first rolled to produce a cathode with a cathode active material layer density of 4.2 g / cc.
[0146] A negative electrode active material layer slurry was prepared by mixing 97.5 wt% of graphite negative electrode active material, 1.5 wt% of carboxymethyl cellulose, and 1 wt% of styrene butadiene rubber in a water solvent. A negative electrode was prepared by coating the negative electrode active material layer slurry onto a copper foil current collector, drying, and rolling.
[0147] A lithium secondary battery was manufactured by a conventional method using an electrolyte in which 1M LiPF6 was dissolved in a solvent mixed with ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7, with a polytetrafluoroethylene separator interposed between the anode and the cathode.
[0148] Example 2
[0149] In the manufacture of a positive electrode active material, a first cobalt transition metal complex oxide having an aluminum content of 5800 ppm (0.58 wt%) is used to produce a first lithium cobalt-based oxide (Li 1.04 Co 0.98 Al 0.02 A first positive electrode active material containing O2 is prepared, and a second lithium cobalt-based oxide (Li) is prepared using a second cobalt transition metal composite oxide having an aluminum content of 7000 ppm (0.70 wt%). 1.02 Co 0.975 Al 0.025 A positive electrode active material and a lithium secondary battery were prepared in substantially the same manner as in Example 1, except that a second positive electrode active material containing O2 was prepared.
[0150] Example 3
[0151] In the manufacture of a positive electrode active material, a first cobalt transition metal complex oxide having an aluminum content of 7300 ppm (0.73 wt%) is used, and a first lithium cobalt-based oxide (Li 1.04 Co 0.974 Al 0.026A first positive electrode active material containing O2 is prepared, and a second lithium cobalt-based oxide (Li2) is prepared using a second cobalt transition metal composite oxide having an aluminum content of 8300 ppm (0.83 wt%). 1.02 Co 0.971 Al 0.029 A positive electrode active material and a lithium secondary battery were prepared in substantially the same manner as in Example 1, except that a second positive electrode active material containing O2 was prepared.
[0152] Example 4
[0153] In the manufacture of a lithium secondary battery, a positive active material and a lithium secondary battery were manufactured in substantially the same manner as in Example 1, except that the first rolled positive was additionally rolled a second time so that the density of the positive active material layer was 4.25 g / cc.
[0154] Comparative Example 1
[0155] A positive electrode active material and a lithium secondary battery were prepared in substantially the same manner as in Example 1, except that CoO2 was used as the first cobalt transition metal composite oxide and the second cobalt transition metal composite oxide in the preparation of the positive electrode active material.
[0156] Comparative Example 2
[0157] In the manufacture of a positive electrode active material, a first cobalt transition metal complex oxide having an aluminum content of 2500 ppm (0.25 wt%) is used to produce a first lithium cobalt-based oxide (Li 1.04 Co 0.991 Al 0.009 A first positive electrode active material containing O2 is prepared, and a second lithium cobalt-based oxide (Li2) is prepared using a second cobalt transition metal composite oxide having an aluminum content of 2500 ppm (0.25 wt%). 1.02 Co 0.991 Al 0.009A positive electrode active material and a lithium secondary battery were prepared in substantially the same manner as in Example 1, except that a second positive electrode active material containing O2 was prepared.
[0158] Comparative Example 3
[0159] In the manufacture of a positive electrode active material, a first cobalt transition metal complex oxide having an aluminum content of 4000 ppm (0.4 wt%) is used to produce a first lithium cobalt-based oxide (Li 1.04 Co 0.988 Al 0.012 A first positive electrode active material containing O2 is prepared, and a second lithium cobalt-based oxide (Li2) is prepared using a second cobalt transition metal composite oxide having an aluminum content of 4000 ppm (0.4 wt%). 1.02 Co 0.988 Al 0.012 A positive electrode active material and a lithium secondary battery were prepared in substantially the same manner as in Example 1, except that a second positive electrode active material containing O2 was prepared.
[0160] Comparative Example 4
[0161] In the manufacture of a positive electrode active material, a first cobalt transition metal complex oxide having an aluminum content of 6000 ppm (0.6 wt%) is used to produce a first lithium cobalt-based oxide (Li 1.04 Co 0.979 Al 0.021 A first positive electrode active material containing O2 is prepared, and a second lithium cobalt-based oxide (Li2) is prepared using a second cobalt transition metal composite oxide having an aluminum content of 6000 ppm (0.6 wt%). 1.02 Co 0.979 Al 0.021 A second positive active material containing O2 was prepared, and a positive active material and a lithium secondary battery were prepared in substantially the same manner as in Example 1, except that Al(OH)3 was not mixed in the step of dry mixing the first positive active material and the second positive active material.
[0163] Evaluation Example 1: Ratio of peak intensity of (006) plane to peak intensity of (101) plane
[0164] X-ray diffraction analysis of the anodes prepared in the examples and comparative examples was performed using Bruker’s Powder XRD (D8 Advance) equipment under the following conditions, where I is the ratio of the peak intensity of the (006) plane to the peak intensity of the (101) plane. 006 / I 101 It was measured and shown in Table 1 below.
[0165] - X-ray wavelength: 1.5406 Å (CuKα1)
[0166] - Slit conditions: Divergence Slit 0.5°, Scattering Slit 0.5°, Receiving Slit 0.20 mm
[0167] - Scan conditions: Continuous Scan, 10°≤2θ≤80°, 0.01° / step, 1.27° / min, total measurement time 55 min.
[0168] Evaluation Example 2: Evaluation of Initial Charge / Discharge Capacity and Efficiency
[0169] The lithium secondary batteries prepared in the examples and comparative examples were charged at 25°C with a constant current of 0.2C to an upper limit voltage of 4.55V and with a constant voltage of 0.05C, and then discharged at 0.2C to a cutoff voltage of 3.0V to perform initial charge and discharge. Table 1 below shows the initial charge capacity, initial discharge capacity, and the ratio of the initial discharge capacity to the initial charge capacity as calculated efficiency.
[0170] Evaluation Example 3: High-temperature life characteristics
[0171] Following the initial charge and discharge of Evaluation Example 2, a cycle of charging at 0.2C and discharging at 0.2C in a voltage range of 3.0V to 4.55V at 45℃ was repeated 50 times or more, and the ratio of the 50-cycle discharge capacity to the initial discharge capacity was calculated and shown in Table 1 below.
[0172] Aluminum content (weight%) of the first positive electrode active material Second positive active material aluminum content (weight%) Cathode active material layer density (g / cc) I 006 / I 101 0.2C charging (mAh / g) 0.2C discharge (mAh / g) Efficiency (%) Lifespan (%, 45℃, 50cycles) Example 1 0.48 0.6 4.2 4.1 208.1 195.2 93.8 85.9 Example 2 0.58 0.7 4.2 4.8 207.6 193.5 93.2 87.4 Example 3 0.73 0.83 4.2 5.1 206.7 191.8 92.8 89.7 Example 4 0.48 0.6 4.25 5.4 208.0 196.6 94.5 90.8 Comparative Example 1 - - 4.2 2.8 211.2 204.2 96.7 50.1 Comparative Example 2 0.25 0.25 4.2 3.2 209.5 200.7 95.8 72.1 Comparative Example 3 0.4 0.4 4.2 3.8 208.7 196.4 94.1 75.4 Comparative Example 4 0.6 0.6 4.2 3.3 207.9 193.7 93.2 82.3
[0173] Referring to Table 1, in the case of Examples 1 to 4, where the aluminum content relative to 100 wt% of the total first cathode active material is 0.4 wt% or more, the aluminum content relative to 100 wt% of the total second cathode active material is 0.5 wt% or more, and Al(OH)3 is used when mixing the first cathode active material and the second cathode active material, I, which is the ratio of the peak intensity of the (006) plane to the peak intensity of the (101) plane 006 / I 101 It can be confirmed that is 4.1 or higher. In contrast, for Comparative Examples 1 to 3, where the aluminum content relative to 100 wt% of the total first cathode active material is less than 0.4 wt% or the aluminum content relative to 100 wt% of the total second cathode active material is less than 0.5 wt%, I, which is the ratio of the peak intensity of the (006) plane to the peak intensity of the (101) plane 006 / I 101 It can be confirmed that α is 3.8 or less. In addition, even in the case of Comparative Example 4, in which Al(OH)3 was not used when mixing the first and second cathode active materials, I 006 / I 101 It can be confirmed that the value is 3.3. At this time, compared to Comparative Examples 1 to 4, it can be confirmed that in the case of Examples 1 to 4, the initial discharge capacity and initial charge / discharge efficiency are maintained within an excellent range while the high-temperature life characteristics are significantly improved.
[0174] In particular, in the case of Example 4, in which the aluminum content of the first positive active material is 0.48 wt% and the aluminum content of the second positive active material is 0.6 wt% and the density of the positive active material layer is 4.25 g / cc after performing rolling twice, it can be confirmed that the initial charge / discharge efficiency and high-temperature life characteristics are the best.
[0175] Although preferred embodiments have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements by those skilled in the art using the basic concepts defined in the following claims are also included within the scope of the present invention. Explanation of the symbols
[0176] 100: Lithium secondary battery 10: Positive electrode 11: Positive lead tab 12: Positive terminal 20: Cathode 21: Cathode lead tab 22: Negative terminal 30: Separator 40: Electrode assembly 50: Case 60: Sealing member 70: Electrode tab 71: Positive tab 72: Negative tab
Claims
Claim 1 A positive electrode comprising: a current collector; and a positive electrode active material layer located on the current collector; wherein the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material comprises: a first positive electrode active material containing a first lithium cobalt-based composite oxide having an aluminum content of 0.4 wt% or more relative to 100 wt% of the total metal excluding lithium; and a second positive electrode active material containing a second lithium cobalt-based composite oxide having an aluminum content of 0.5 wt% or more relative to 100 wt% of the total metal excluding lithium; and the average particle size (D) of the first positive electrode active material 50 ) is the average particle size (D) of the second positive active material above. 50 An anode that is greater than ) and, with respect to the total sum of the first and second anode active materials of 100 wt%, comprises 70 wt% to 90 wt% of the first anode active material and 10 wt% to 30 wt% of the second anode active material, and has a ratio of the peak intensity of the (006) plane to the peak intensity of the (101) plane when measuring the X-ray diffraction pattern of the anode to 4.0 or more. Claim 2 In claim 1, the first lithium cobalt-based composite oxide is an anode represented by the following chemical formula 1: [Chemical Formula 1]Li a1 Co x1 Mg y1 Al z1 M 1 w1 O 2-b1 X b1 In Chemical Formula 1, 0.8≤a1≤1.5, 0.9≤x1≤0.99, 0≤y1≤0.05, 0.01≤z1≤0.04, 0≤w1≤0.01, 0.9≤x1+y1+z1+w1≤1.1 and 0≤b1≤0.1, and M 1 is one or more of the elements B, Ba, Ca, Ce, Cr, Cu, Fe, Mn, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, Zn and Zr, and X is one or more of the elements F, P and S. Claim 3 A cathode according to claim 1, wherein the aluminum content is 0.4 weight% to 2.0 weight% relative to 100 weight% of the total metal excluding lithium in the first lithium cobalt-based composite oxide. Claim 4 In claim 1, the average particle size (D) of the first positive active material 50 An anode having a thickness of 9 μm to 30 μm. Claim 5 In claim 1, the second lithium cobalt-based composite oxide is an anode represented by the following chemical formula 1: [Chemical Formula 2]Li a2 Co x2 Mg y2 Al z2 M 2 w2 O 2-b2 X b2 In Chemical Formula 2, 0.8≤a2≤1.5, 0.9≤x2≤0.99, 0≤y2≤0.05, 0.01≤z2≤0.04, 0≤w2≤0.01, 0.9≤x2+y2+z2+w2≤1.1 and 0≤b2≤0.1, and M 2 is one or more of the elements B, Ba, Ca, Ce, Cr, Cu, Fe, Mn, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, Zn and Zr, and X is one or more of the elements F, P and S. Claim 6 A cathode according to claim 1, wherein the aluminum content is 0.5 weight% to 2.0 weight% relative to 100 weight% of the total metal excluding lithium in the second lithium cobalt-based composite oxide. Claim 7 In claim 1, the average particle size (D) of the second positive active material 50 An anode having a thickness of 1 μm to 9 μm. Claim 8 An anode according to claim 1, wherein the ratio of the peak intensity of the (006) plane to the peak intensity of the (101) plane when measuring the X-ray diffraction pattern of the anode is 4.0 to 6.
0. Claim 9 In claim 1, the loading level of the positive electrode active material layer is 10 mg / cm² 2 to 40 mg / cm² 2 Phosphorus anode. Claim 10 A positive electrode according to claim 1, wherein the density of the positive electrode active material layer is 4.2 g / cc to 4.5 g / cc. Claim 11 In claim 1, the positive active material layer further comprises aluminum hydroxide, aluminum oxide, or a combination thereof. Claim 12 (i) a step of preparing a first positive electrode active material containing a first lithium cobalt-based oxide having an aluminum content of 0.4 wt% or more relative to 100 wt% of the total metal excluding lithium; (ii) containing a second lithium cobalt-based oxide having an aluminum content of 0.5 wt% or more relative to 100 wt% of the total metal excluding lithium, and the average particle size (D) of the first positive electrode active material 50 Average particle size (D) compared to ) 50 A method for manufacturing an anode comprising: a step of preparing a second anode active material; (iii) a step of preparing an anode composition by mixing 70% to 90% by weight of the first anode active material, 10% to 30% by weight of the second anode active material, and Al(OH)3 with respect to a total of 100% by weight of the first anode active material and the second anode active material; (iv) a step of manufacturing an anode by coating and drying the anode composition on a current collector; and (v) a step of first rolling the anode. Claim 13 A method for manufacturing an anode according to claim 12, further comprising the step of rolling the first rolled anode a second time. Claim 14 A method for manufacturing a positive electrode according to claim 12, wherein in step (iii) above, Al(OH)3 is mixed in an amount of 0.01% to 0.1% by weight relative to 100% by weight of the total of the first positive electrode active material and the second positive electrode active material. Claim 15 A method for manufacturing an anode according to claim 12, wherein the ratio of the peak intensity of the (006) plane to the peak intensity of the (101) plane when measuring the X-ray diffraction pattern of the rolled anode is 4.0 to 6.
0. Claim 16 A method for manufacturing an anode according to claim 12, wherein the density of the anode active material layer in the rolled anode is 4.2 g / cc to 4.5 g / cc. Claim 17 A lithium secondary battery comprising a positive electrode; a negative electrode; and an electrolyte according to any one of claims 1 to 11.